Aspirin use and the risk of bleeding complications after therapeutic bronchoscopy - Harris, Kassem (Ther Adv Respir Dis, 2016)
BACKGROUND: Aspirin use has been shown to be safe for patients undergoing certain diagnostic bronchoscopy procedures such as transbronchial biopsies and endobronchial ultrasound (EBUS)-guided transbronchial needle aspiration. However, there are no studies documenting the safety of aspirin in patients undergoing therapeutic bronchoscopy. The aim of this study is to evaluate whether aspirin increases the risk of bleeding following therapeutic bronchoscopy. METHODS: This was a retrospective study to determine if there was a higher risk of bleeding in patients on aspirin undergoing therapeutic bronchoscopy compared with those not on aspirin. Patient characteristics were reported by cohort using the mean, median, and standard deviation for continuous variables, and using frequencies and relative frequencies for categorical variables. RESULTS: Of the 108 patients who had multimodality therapeutic bronchoscopy, 17 (15.7%) were taking aspirin and 91 (84.3%) were not on aspirin. Patients in the aspirin group were older than those in the no aspirin group (median age: 66 versus 60 years, p = 0.007). The treatment modalities were similar in both groups except that more patients in the no aspirin group were treated with argon plasma coagulation (APC) compared to the aspirin group (60.4% versus 29.4%, p = 0.031). The estimated blood loss (EBL) between the aspirin and no aspirin groups was not significantly different (mean: 6.0 versus 6.7 ml; median: 5.0 versus 5.0, p = 0.36). Overall, there was no difference in complications between both groups. CONCLUSION: Aspirin use was not associated with increased risk of bleeding or procedure-related complications after therapeutic bronchoscopy.